Darling sweetheart: Queer objects in early computer art. Issue 1 (1st December 2013) - Gaboury, Jacob
Reaching back to the very origins of modern computing, this article seeks to identify one of the earliest examples of expressive computational art ever produced in the queer work of the computer scientist Christopher Strachey. Strachey was a colleague of computer pioneer Alan Turing, and the author of several playful early programs for computer music, computer games, and computer fiction. In examining his work through the lens of computer art and sexuality, this article argues for the role of playful misuse, mischievous disruption, and the unexpected in the production of new forms of expressive computational art that we might describe as a new romanticism.